DESKRIPSI KETERAMPILAN BERPIKIR KRITIS MAHASISWA PENDIDIKAN KIMIA FKIP UNTAN - Suliono, .; Enawaty, Eny; Rasmawan, Rahmat (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This research is based on the importance of critical thinking skills in the teaching and learning of Chemistry. The purpose of this research is to describe the critical thinking skills possessed by the students of Chemistry Education of Teachers Training and Education Faculty of Tanjungpura University. The subject of this research is the sixth semester students of Chemistry Education of Teachers Training and Education Faculty of Tanjungpura University. The type of this research is descriptive research and it applies survey method. The research instrument is critical thinking test skills of Watson Glaser Critical Thinking Appraisal. The result of the critical thinking skills is as follows: that 37.5% students is able to analyze the arguments at the advanced level; 50% students is able to interpret the information at the advanced level; 56.25% students is able to evaluate the assumption at the advanced level; 68.75% students is able to conduct the generalization at the advanced level; and 62.5% students is able to draw a conclusion at the advanced level. It means the critical thinking skills of the sixth semester students of Chemistry Education of Teachers Training and Education Faculty of Tanjungpura University at the advanced level. Keywords: Watson-Glaser, Critical Thinking Skills, the Students of Chemistry Education